ANALISIS KETERKAITAN BAURAN PEMASARAN DENGAN TINGKAT KEPUASAN KONSUMEN UKM PENGAIS JAYA VIRGIN COCONUT OIL DI DESA AMPIBABO - lina, Nur; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2013)
The purpose of this study was to determine the effect of the marketing mix (product, price, promotion and distribution) and level of customer satisfaction of UKM Pengais Jaya Virgin Coconut Oil (VCO) in the AmpibaboVillage Sub District Ampibabo DistrictMoutong Parigi. Data were analysed with Fisher 's exact probability test analysis (p) and chi square (x2). The results showed a relationship of the marketing mix and customer satisfaction level by using the confidence interval of 95 % or ? = 0.05 which obtained marketing mix (product , price, promotion and distribution ) in UKM Pengais Jaya affect the level of consumer satisfaction. Either partially (individual) or colectively, so marketing mix had a significant relationship to consumer satisfaction, especially the marketing mix (product and price).